A review of psychotherapeutic models and treatments for psychosis. Issue 3 (3rd July 2019) - Ridenour, Jeremy M.; Hamm, Jay A.; Czaja, Meg
ABSTRACT: Despite long-standing pessimism, it is now widely recognized that individuals with psychosis can recover if offered meaningful psychotherapeutic treatments. This paper provides an overview of psychotherapeutic approaches and models for treatment for individuals who experience psychosis. We selected psychotherapeutic models from diverse theoretical orientations (e.g. cognitive-behavioral, acceptance and commitment therapy, psychodynamic, and integrative) to highlight different treatment philosophies and models for interventions. Although some of these therapies have yet to establish an empirically supported evidence base, they have been selected for review in light of their respective emerging literatures and because they offer distinct methods of understanding and treating severe 'mental illness'. This review article provides clinicians with different approaches to treatment that will allow them to explore various interventions to provide integrative care for individuals experiencing psychosis. This paper indicates that evidence-based psychotherapies for psychosis are just emerging and that newer therapies should be considered to provide a range of treatment options. More research is needed to develop efficacious treatments that not only alleviate distress but also promote meaningful recovery for individuals with psychosis.